2014
DOI: 10.1038/ng.3143
|View full text |Cite
|
Sign up to set email alerts
|

Variation at HLA-DRB1 is associated with resistance to enteric fever

Abstract: Enteric fever affects more than 25 million people annually and results from systemic infection with Salmonella enterica serovar Typhi or Paratyphi pathovars A, B or C1. We conducted a genome-wide association study of 432 individuals with blood culture–confirmed enteric fever and 2,011 controls from Vietnam. We observed strong association at rs7765379 (odds ratio (OR) for the minor allele = 0.18, P = 4.5 × 10−10), a marker mapping to the HLA class II region, in proximity to HLA-DQB1 and HLA-DRB1. We replicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 56 publications
5
76
0
Order By: Relevance
“…Patients with enteric fever and the protective haplotype were shown to produce statistically significantly less TNF ex vivo on whole blood stimulation with LPS on day four of disease 59 . However, this finding should be interpreted with caution, as this effect was not seen in a better-powered GWAS of enteric fever in the same population 6 .…”
Section: Haematocritmentioning
confidence: 76%
“…Patients with enteric fever and the protective haplotype were shown to produce statistically significantly less TNF ex vivo on whole blood stimulation with LPS on day four of disease 59 . However, this finding should be interpreted with caution, as this effect was not seen in a better-powered GWAS of enteric fever in the same population 6 .…”
Section: Haematocritmentioning
confidence: 76%
“…Further analysis of the Vietnamese population again suggested that a haplotype in the TNF region gives protection against enteric fever, but the causative disease locus remains to be determined (32). In a recent genome-wide association study of patients in Vietnam and Nepal with blood culture-confirmed enteric fever, a strong association was found for HLA-DRB1 as a major contributor to resistance against enteric fever, presumably through antigen presentation (33).…”
Section: Epidemiology and Clinical Aspects Typhoidal Salmonellamentioning
confidence: 99%
“…More importantly, the co-occurrence of type-1 diabetes and celiac disease [53] in the same patients was linked to HLA-C exemplifying both genetic predisposition as well as coexistence of two immunologic phenomena. Taken together, these associations between HLA subgroups and autoimmunity are believed to represent a hyperactive immune system with the disadvantage of autoimmunity risk in one hand and an evolutionary advantage in fighting infections, such as enteric fever [54]. In addition to the genetic predisposition, environmental factors have also been linked to autoimmunity.…”
Section: Patients With History Of Allergic Conditions/atopic Disordersmentioning
confidence: 99%